2008
DOI: 10.1097/meg.0b013e3282f945fb
|View full text |Cite
|
Sign up to set email alerts
|

Expression of COX-2 is associated with accumulation of p53 in pancreatic cancer: analysis of COX-2 and p53 expression in premalignant and malignant ductal pancreatic lesions

Abstract: These findings confirmed the generally accepted pancreatic cancer progression model, and supported the concept of the interactive role of COX-2 and p53 in pancreatic cancer carcinogenesis, which offers opportunities for targeted therapy and chemoprevention of pancreatic cancer using COX-2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…It is inactivated largely via mutation, usually resulting in nuclear accumulation and positive IH stain [23][24][25] . The p53 abnormality is detected in 50% to 90% of pancreatic adenocarcinomas [23][24][25][26][27][28][29][30][31] , and in their precursor, PanIN, the positive stain ing is directly correlated to the grade [17,[29][30][31] . Our findings agree with previous studies on EUS-FNA of pancreas, which showed that the addition of p53 IH or DNA analysis resulted in a modest sensitivity gain [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…It is inactivated largely via mutation, usually resulting in nuclear accumulation and positive IH stain [23][24][25] . The p53 abnormality is detected in 50% to 90% of pancreatic adenocarcinomas [23][24][25][26][27][28][29][30][31] , and in their precursor, PanIN, the positive stain ing is directly correlated to the grade [17,[29][30][31] . Our findings agree with previous studies on EUS-FNA of pancreas, which showed that the addition of p53 IH or DNA analysis resulted in a modest sensitivity gain [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…They supported the possible role of COX-2 in carcinogenesis of pancreatic ductal adenocarcinoma. It has been suggested that PanINs represent the possible link between chronic pancreatitis and pancreatic cancer and that COX-2 may represent a possible therapeutic target for potential chemoprevention in patients with chronic pancreatitis and pancreatic ductal adenocarcinoma using selective COX-2 inhibitors [35,36,37]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified that the COX-2 expression is significantly correlated with the tumor size in pancreatic cancer, which offers a new insight into the regulation of growth and development of metastases in pancreatic cancer [39] . A correlation between COX-2 and p53 expression levels in carcinomas was revealed, and an accumulation of p53 was associated with COX-2 overexpression in premalignant and malignant ductal lesions, which offers opportunities for targeted therapy and chemoprevention of pancreatic cancer using COX-2 inhibitors,especially in lesions with functional p53 [40] .…”
Section: Cox-2mentioning
confidence: 97%